Realismo, moralidade e poder: um estudo comparativo entre Morgenthau e Kissinger na política externa dos EUA - Almeida, João (Universidade Federal de São Carlos, 2025)
This study aims to comparatively analyze the concepts of power and morality in the thoughtof Hans Morgenthau and Henry Kissinger, focusing on their implications for United Statesforeign policy. The research adopts a theoretical and qualitative approach, using thecomparative analysis method to identify convergences and divergences between the authors.Initially, it examines Morgenthau’s theoretical foundations, highlighting his classical realistconception, especially the notions of national interest, power, and the tension with morality.Then, it analyzes Kissinger’s thought, emphasizing his pragmatic realism, the practicalapplication of his ideas as a statesman, and his historical perspective on internationalrelations. In the final chapter, the study contrasts both authors’ views, identifying how eachinterprets the role of morality in international politics, as well as their differingunderstandings of the use and function of power within the context of U.S. foreign policy. Theconclusion points out that, although both share a realist foundation, their approaches differsignificantly: Morgenthau constructs a normative theory on the moral limits andresponsibilities of power, while Kissinger adopts a more strategic and situational stance,prioritizing international stability and balance. The analysis contributes to understanding howdifferent strands of realism shape distinct views on state behavior, enriching the debate on therole of the United States in the contemporary international order.
Realism, morality, and power: a comparative study of Morgenthau and Kissinger in U.S. foreign policy
Keywords: Realismo político; Hans Morgenthau; Henry Kissinger; Política externa; Poder; Foreign policy; Power; CIENCIAS HUMANAS::CIENCIA POLITICA::TEORIA POLITICA